Analisis Celah Haram dalam Sistem Permodalan Bank Umum Syariah Berdasarkan Peraturan OJK Nomor 16/POJK.03/2022 - Qian Ramadhani; Vincent Anderson Simanjutntak; Elvira Clarista Faiqah; Rodhia Tammardhiah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Islamic Commercial Banks operate under Islamic law, necessitating compliance with sharia principles from their inception to their operations, including capital system. This study investigates potential haram loopholes in the capital system of Islamic Commercial Banks, specifically in light of OJK Regulation Number 16/PJOK.03/2022. Utilizing a normative legal research methodology with a legislative approach, the findings reveal a significant loophole regarding the capital system. Article 31 of the regulation does not stipulate that the sources of funds for paid-up capital in Islamic Commercial Banks must adhere to sharia principles. This contrasts with the previous Bank Indonesia Regulation No. 6/24/PBI/2004, which explicitly required that capital sources for Islamic Commercial Banks be halal and not derived from haram sources. The omission of this requirement in the current Financial Services Authority regulation raises concerns about the integrity of capital in Islamic Commercial Banks, as it lacks a safeguard ensuring that the capital originates from permissible sources. This gap could potentially lead to unauthorized practices and undermine the fundamental principles of Islamic finance.